Inovasi Produk dan Citra Merek: Penggerak Keputusan Pembelian pada Sentra Olahan Salak Kunara - Aprilia, Yayang Inggrit Putri; Mahendri, Wisnu (Universitas KH. A. Wahab Hasbullah, 2025)
Salak Kunara Processing Center, a food industry in Jombang, focuses on salak processing. The rapid growth of the food and beverage industry demands product innovation and a strong brand image to compete and attract consumers. This study aims to find out how product innovation and brand image affect consumer purchase decisions at the Salak Kunara Processing Center in Kedungrejo Village, Jombang. This study used a quantitative method with a questionnaire distributed to 110 respondents. The data was analyzed with linear regression to test the hypothesis and measure how much influence these variables have. The results show that product innovation and brand image both have a positive and significant effect on purchasing decisions. This shows that sustainable product innovation and a strong brand image are essential to improve the competitiveness of local food products.